Cavity-Enhanced Spectroscopy in Condensed Phases: Recent Literature and Remaining Challenges - Jonathan E. Thompson (Journal of Spectroscopy)
Recent developments in the field of cavity-enhanced spectroscopy (CES) on liquid samples are presented. The various experimental approaches to achieving the measurements are summarized, and the limitations of each approach are discussed. I conclude CES is most promising for microscale light absorption measurements on submicroliter volumes of fluid.